(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) administered as initial therapy enhance the quality of life for individuals diagnosed with EGFR mutation-sensitive non-small cell lung cancer (NSCLC). Our investigation focused on evaluating treatment outcomes among patients with EGFR-mutant NSCLC who exhibit concurrent gene alterations, aiming to ascertain their predictive significance regarding response to EGFR-TKIs treatment. Materials and Methods: A retrospective cohort study was conducted the next gene sequencing (NGS) data from January 2019 to Jun 2023. All patients were categorized into two groups: One comprising individuals with a single EGFR mutation (group 1), and the other consisting of patients with concurrent EGFR mutations (group 2). Results: 109 patients with EGFR mutation showed 72 patients had partial responses (66.1%), one had complete response (0.9%) and 17 patients had stable disease (15.6%); 19 patients had progressive disease (17.4%). The ORR was 67% and DCR was 82.6%. The PFS in the group with single EGFR mutation and concurrent gene alterations group were 15.03 months (CI 95%: 13.17-16.89) and 11.00 months (CI 95%: 9.95-12.05) (p= 0.001). Among the 43 patients with concomitant mutations, patients with ALK mutation had the longest PFS (13.43 months), followed by other PIK3CA (11.00 months) and the lowest PFS was MET application (4.77 months). Conclusion: This study has demonstrated the concurrent gene alterations in some patients with EGFR mutations, which leads to reduced outcome of EGFR-TKIs. Patients carrying KRAS, BRAF, ROS1, or MET mutations are considered to have less predictive value for positive treatment outcomes.